THE LAW AND CONTRACT: WHICH ONE IS IN A HIGHER LEGAL POSITION? - Ruslan Kholmatov (Modern American Journals, 2025)
This article examines the relationship between law and contract within the civil law systems of Uzbekistan, Russia, Ukraine, and the United States. The study explores how the principles of freedom of contract and supremacy of law interact in regulating civil and commercial relations. Drawing on legislative acts, judicial practice, and academic literature, the author analyzes the temporal effect of laws, the scope of contractual autonomy, and the legal consequences of contractual violations. The comparative analysis demonstrates that, despite differences in legal systems, all jurisdictions strive to maintain a balance between contractual flexibility and legal stability. Special attention is given to how courts interpret and apply these principles in practice to ensure fairness and predictability in contractual relations.
Keywords: Law, contract, civil law, contractual freedom, supremacy of law, Uzbekistan, Russia, Ukraine, United States, civil code, comparative law, legal stability, judicial practice, contractual liability.